Observing Students' Engagement in Rural Indonesian EFL Classrooms Through The “Word of the Day” Strategy - Ashar, Aisyah; Khartha, Aqzhariady; Abin, Rais; Suryadi, Ray (Jurnal Paedagogy, 2025)
This study aimed to investigate the effectiveness of the Word of the Day (WotD) strategy in enhancing vocabulary learning and student engagement in a rural EFL context. A quasi-experimental control class (CC) design was employed, involving two ninth-grade classes from SMP Negeri 2 Samaturu. Class 9A received instruction using the WotD-based approach, while Class 9E was taught using traditional methods. Data were collected through pre- and post-tests, classroom observations, semi-structured interviews, and open-ended questionnaires. The WotD strategy was implemented in several stages, including a pre-test, strategy application through contextual texts and games, and a post-test. Quantitative data were analyzed by comparing mean scores between groups, whereas qualitative data were analyzed thematically. The results indicated that vocabulary scores significantly improved in Class 9A (mean gain = 23.3) compared to Class 9E (mean gain = 9.2), along with higher levels of classroom participation. These findings suggest that low-stakes vocabulary strategies such as WotD can effectively promote vocabulary acquisition and active participation in under-resourced rural classrooms. Complementary qualitative findings further highlighted the roles of family support, student motivation, and peer collaboration in enhancing classroom engagement beyond test performance.